2019
DOI: 10.14807/ijmp.v10i1.839
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y’s Complaint Behavior toward Online Shopping

Abstract: The purpose of this research was to analyze factors that influence Generation Y’s complaint behavior in online shopping. In general, Generation Y’s consumer of this research have a good perception of consumer rights. In contrast, the result showed that Generation Y in this research had a low complaint behavior. The research found that gender, strivers lifestyle, and number of social media account were influence Generation Y’s complaint behavior in online shopping. The result showed that male student did more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
4
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
2
14
4
7
Order By: Relevance
“…Return policy (23.0%) and money guarantee (23.0%) also had a large percentage of shipping expedition services. This study in line with Simanjuntak (2019) that the causes of online shop complain was late delivery, wrong size, wrong color, and when the product is not in accordance with the promised conditions. They often tell close friends and family members, when they disappointed.…”
Section: Complaint Behaviorsupporting
confidence: 83%
See 1 more Smart Citation
“…Return policy (23.0%) and money guarantee (23.0%) also had a large percentage of shipping expedition services. This study in line with Simanjuntak (2019) that the causes of online shop complain was late delivery, wrong size, wrong color, and when the product is not in accordance with the promised conditions. They often tell close friends and family members, when they disappointed.…”
Section: Complaint Behaviorsupporting
confidence: 83%
“…According to Peacock and Eatough (2012), consumer empowerment is the idea that consumers must have the tools to secure the best outcome for themselves. Some research results concluded that factors affecting empowerment include education (NARDO et al, 2011; SIMANJUNTAK; YULIATI, 2015; SIMANJUNTAK; PUTRI, 2018), occupations (GHOLIPOUR, 2010), age (NARDO et al, 2011;PUTRI, 2018), gender (MIDHA, 2012;YULIATI, 2016), ethnic (NARDO et al, 2011, geographical location , and revenues (NARDO et al, 2011), these factors are further classified into several characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A statistically significant gender difference was evident in the online bike service usage (p < 0.05), that supported by. Several researches showed that gender associated with behavior (Hartatin & Simanjuntak, 2016;Jeddawi et al, 2019;Simanjuntak, 2019;Simanjuntak & Dewantara, 2014;Simanjuntak, 2020;Simanjuntak & Musyifah, 2016).…”
Section: Descriptive Analysis Of Respondent Characteristics and Research Variablesmentioning
confidence: 99%
“…Penelitian sebelumnya hanya meneliti hubungan variabel terhadap pembelian impulsif. Penelitian ini melihat tiga faktor yang memengaruhi proses keputusan konsumen, dalam hal ini pembelian impulsif, yaitu faktor konsep diri, gaya hidup, dan strategi pemasaran dengan menganalisis perbedaan pengaruh variabel pada tiga generasi yaitu generasi baby boomer, generasi X, dan generasi Y. Beberapa riset konsumen yang mengkaji secara spesifik generasi adalah Simanjuntak (2019) Variabel/dimensi/indikator dikategorikan menjadi rendah, sedang, dan tinggi dengan melakukan transformasi skor asli (skor 1-4) yang kemudian dijumlahkan lalu dibuat indeks 0-100. Skor indeks tersebut kemudian digolongkan ke dalam tiga kriteria sebagai berikut tinggi dengan skor >80-100, sedang dengan skor 60-80, dan rendah dengan skor 0-<60.…”
unclassified